Fulfilment of the Right to Health for Elderly Prisoners (Study at Class IIA Ambarawa Correctional Institution) - Fanny Jeane; Marcella Elwina Simandjuntak; Hady Sulistyanto (SOEPRA, 2021)
Abstract: This study with the title Fulfillment of the Right to Health for Elderly Prisoners (Study at Penitentiary Class II A Ambarawa) aims to determine the fulfilment of the right to health of elderly prisoners and the obstacles faced by correctional institutions in fulfilling the right to health for elderly prisoners. This research was conducted at the Class IIA Ambarawa Correctional Institution.The approach method used is qualitative. Data were collected by interview and literature study. Data analysis was carried out qualitatively.Based on the results of research and discussion, it can be seen that the Penitentiary has so far been trying to fulfil the right to health for elderly prisoners. This can be reflected in the existing facilities and infrastructure in the form of treatment centres, the availability of simple medical equipment, the availability of medicines, the implementation of health services, the provision of food according to nutritional standards, and sports activities that have been scheduled by the Correctional Institution. For prisoners who need further treatment if their health conditions require more serious treatment, there is cooperation in health services with a local hospital, namely RSUD Ambarawa. However, in reality, the fulfilment of the right to health for elderly prisoners is hampered/constrained by several things including the lack of medical personnel, the lack of quantity and quality of medicines and the lack of available medical equipment.To overcome various obstacles, the suggestion from the researcher is that the Class IIA Ambarawa Correctional Institution applies for an increase in the quota of prison medical personnel, the provision of more complete and quality medicines and medical equipment so that the Correctional Institution has no difficulty in handling and fulfilling the right to health. for elderly prisoners.Abstrak: Penelitian dengan judul Pemenuhan Hak atas Kesehatan  bagi Narapidana Lanjut Usia (Studi di Lembaga Pemasyarakatan Kelas II A Ambarawa) ini bertujuan untuk mengetahui  pemenuhan hak atas kesehatan narapidana lanjut usia dan kendala yang dihadapi Lembaga Pemasyarakatan dalam memenuhi hak atas kesehatan bagi narapidana lanjut usia. Penelitian ini dilaksanakan di Lembaga Pemasyarakatan Kelas IIA Ambarawa.Metode pendekatan yang digunakan adalah metode kualitatif. Data dikumpulkan dengan teknik wawancara dan studi pustaka. Analisis data dilakukan secara kualitatif.Berdasarkan hasil penelitian dan pembahasan dapat diketahui bahwa pihak Lembaga Pemasyarakatan sejauh ini telah berupaya memenuhi hak atas kesehatan bagi narapidana lanjut usia.  Hal tersebut dapat tercermin dari adanya sarana dan prasana yang telah tersedia yang berupa adanya balai pengobatan, tersedianya peralatan medis sederhana, tersedianya obat-obatan, terselenggaranya pelayanan kesehatan, pemberian makanan sesuai dengan standar gizi, dan kegiatan olahraga yang telah dijadwalkan oleh Lembaga Pemasyarakatan. Untuk narapidana yang membutuhkan perawatan lanjutan jika kondisi kesehatan membutuhkan perawatan lebih serius, terdapat kerja sama pelayanan kesehatan dengan Rumah Sakit setempat yaitu RSUD Ambarawa. Namun  dalam realisasinya, pemenuhan hak atas kesehatan bagi narapidana lanjut usia terhambat/terkendala oleh beberapa hal diantaranya  minimnya jumlah tenaga medis, minimnya jumlah dan kualitas obat-obatan serta minimnya peralatan medis yang tersedia.Untuk mengatasi berbagai kendala, saran dari Peneliti adalah agar pihak Lembaga Pemasyarakatan Kelas IIA Ambarawa mengajukan permohonan penambahan kuota tenaga medis Lapas, penyediaan obat-obatan serta peralatan medis yang lebih lengkap dan bermutu, agar pihak Lembaga Pemasyarakatan tidak kesulitan dalam menangani dan memenuhi hak atas kesehatan bagi para narapidana lanjut usia.